Interstitial Pregnancy in the Third Trimester with Severe Preeclampsia: A Case Report and Literature Review - Shiho Nagayama; Hironori Takahashi; Shohei Tozawa; Risa Narumi; Rie Usui; Akihide Ohkuchi; Shigeki Matsubara (Hindawi Limited, 2020)
An interstitial pregnancy that continues beyond the second trimester is a rare phenomenon. We report a patient with an interstitial pregnancy undiagnosed until the third trimester. A multiparous woman was referred to us because of preeclampsia at 26 weeks of gestation. The placental position was the right fundus, and color Doppler ultrasound revealed myometrial thinning and subplacental hypervascularity, leading to a suspicion of placenta accreta spectrum (PAS). Emergency cesarean section was performed at 281/7 weeks of gestation due to severe preeclampsia. The right tubal horn to the isthmus of the fallopian tube bulged with placental adhesion and a part of the tube had ruptured, with the omentum adhering to the ruptured part. Interstitial and tubal isthmic pregnancy with uterine rupture was diagnosed.